Sleep, Anxiety, and Academic Performance: A Study of Adolescents From Public High Schools in China - Zhang, Xiaoning; Dimitriou, Dagmara; Halstead, Elizabeth J. (Frontiers in Psychology, 2021)
Purpose: Sleep is essential for optimal learning across the developmental pathways. This study aimed to (1) explore whether school start and end times and screen time influenced sleep disturbances in adolescents during the lockdown in China and (2) investigate if sleep disturbances at night and sleep-related impairment (daytime fatigue) influenced adolescents’ academic performance and anxiety levels. Methods: 99 adolescents aged 15-17 years old were recruited from two public schools in Baishan City Jilin Province, China. An online questionnaire was distributed including questions on adolescents’ demographics, screen time habits, academic performance, anxiety level, sleep disturbances and sleep-related impairment. Results: Adolescents who started school earlier and ended school later had a greater severity of sleep disturbances and sleep-related impairment compared with students who started school later and finished earlier. Adolescents who engaged in screen time at bedtime were more likely to have a greater severity of sleep-related impairment than students who reported no screen time use at bedtime. Adolescents who had a greater severity of sleep disturbances had higher anxiety and higher academic achievements than adolescents with less sleep disturbances. Finally, 79.7% of adolescents reported their total sleep duration as <8 hours. Conclusions: Adolescents are experiencing sleep disturbances to manage academic demands during COVID-19, which in turn is having a wider impact on their mental health. Many schools internationally have continued to provide online education to students, longitudinal studies on how COVID-19 has influenced adolescents sleep and mental health would be beneficial in understanding the impact of the pandemic.